International Seminar on Software Engineering Computer Systems 2011 - UMP, . (Faculty of Computer Systems and Software Engineering, 2011)
Faculty of Computer Systems & Soft ware Engineering (FSKKP) Universiti Malaysia Pahang (UMP) in collaboration with the Information Society Digital and Wireless Communications (SDIWC) had organized the International Seminar on Software Engineering Computer Systems 2011 (ICSECS'ʹ11) at UMP Gambang. This is the second seminar, themed "ʺFostering the rapid innovation in ICT"ʺ is the best platform for researchers to present research findings and share experiences on the application, discovery and new technology involves the field of software engineering and computer science”.